Cost‐effectiveness of hydrophilic‐coated urinary catheters for individuals with spinal cord injury: A systematic review. Issue 2 (20th December 2020) - Xi, Min; Elterman, Dean S.; Welk, Blayne; Pakosh, Maureen; Chan, Brian C. F.
Abstract: Objective: To identify and critically evaluate the economic evaluations examining the cost‐effectiveness of hydrophilic‐coated vs uncoated catheters for individuals with spinal cord injury. Methods: We searched MEDLINE, the Excerpta Medica database (EMBASE), Cochrane Database of Systematic Reviews, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Emcare for studies in English and French. There were no restrictions to the year of publication. Our search strategy included the following key terms: "spinal cord injury, " "catheterization, " and "cost analysis." Results: The search identified 371 studies, of which eight studies met the inclusion criteria. Five studies observed hydrophilic‐coated catheters to be cost‐effective compared to uncoated catheters. Two studies found hydrophilic‐coated catheters to be not cost‐effective compared to uncoated catheters and one study estimated that hydrophilic‐coated catheters reduced the long‐term health‐care costs compared to uncoated catheters. Conclusion: The cost‐effectiveness of hydrophilic‐coated catheters was dependent on the comparator used, the consideration of long‐term effects, and the unit cost of treatment. Further studies are needed to explore the short‐term and long‐term effects of hydrophilic‐coated catheter use on urinary tract infections and clarify the impact of hydrophilic‐coated catheter use on long‐term renal function. Overall, our critical evaluation of the literature suggests that the evidence is pointing toward hydrophilic‐coated catheters being cost‐effective, particularly when a societal perspective is applied.